Analisis Kesiapan Pemerintahan Kota Prabumulih Dalam Implementasi E-Government Menggunakan Metode Technology Readiness Index (TRI) - Nisa Aprina Maris; Eka Puji Agustini; Megawaty Megawaty; Tri Oktarina (Journal of Information System Research (JOSH), 2023)
E-government s an nformation technology system developed by the government to mprove public services by providing choices to the public to get easy access to public nformation. For this reason, socialization of e-government needs to be carried out consistently, continuously and with ncentives to the community because the community does not yet understand what and how e-government applications are and the benefits they can get. The problem that occurs at this time s that t s not known how far the level of readiness of the Prabumulih City Government s n the use and application of nformation technology, especially E-Government. Because of this, t s necessary to carry out an analysis or assessment of the readiness to apply nformation technology, n this case the Government of Prabumulih City. The solution offered s to carry out a readiness analysis using the TR method or Technology Readiness (TR) which s a person's tendency to want to use a new technology that aims to achieve everyday life or n the workplace. Meanwhile, the Technology Readiness ndex s an ndex used to measure the readiness of new technology users to achieve goals n everyday life and work. n order to support the Government of Prabumulih City to carry out eGovernment mplementation with the help of nformation and communication technology, t opens new opportunities to further explore nformation so that t can be utilized optimally. E-Government users cover a wide population, both for government, citizens and business people, so that n the end a mutually beneficial relationship s created. The results obtained from this study are Optimism has a value of 1.51, nnovativeness has a value of 1.24, Discomfort has a value of 0.69 and nsecurity has a value of 0.64. The total results show that the relevant agencies are ready to mplement technology.